Quantitative hybridization-arrest of mRNA in Xenopus oocytes using single-stranded complementary DNA or oligonucleotide probes. - Kawasaki, E S (1985)
The expression of heterologous mRNA in Xenopus oocytes was quantitatively inhibited by coinjection of single-stranded complementary DNA or synthetic complementary oligonucleotides. The lymphokines Interleukin-2 (IL-2) and Interleukin-3 (IL-3) were used as model systems to test the effectiveness of this procedure. Messenger RNA samples were hybridized to single stranded complementary DNA or oligonucleotides, injected into oocytes and the oocyte incubation medium assayed for the presence or absence of specific translation products 48 hours later. When IL-2 mRNA was hybridized to a large excess of long (490 bases) single stranded complementary DNA, the expression of IL-2 was effectively blocked (greater than 98%). Complementary oligonucleotides (18-23 bases) were almost as effective as the polynucleotide in inhibiting IL-2 activity (greater than 95%). Oligonucleotides derived from the 5' end, middle or 3' end of the coding sequence were all effective in arresting IL-2 mRNA translation. Oligonucleotide hybrid-arrest was effective even when no NaCl was present in the hybridization buffer, indicating that the annealing reaction could occur within the oocyte after injection. Definite proof that hybrid-arrest could occur in vivo was shown by the fact that oligonucleotides injected before or after mRNA injection, while not as effective as co-injection, still showed substantial inhibition of specific mRNA translation. The oligonucleotide hybrid-arrest method was equally effective in the case of IL-3, demonstrating its general applicability.